Evaluation of the inclination effect of non-splinted implants on the prosthetic behavior of overdentures in mandible edentulous patients - Aristizabal-Hoyos, Juan Alberto; Restrepo-Herrera, Luis Alejandro; Gálvez-Reyes, Camilo Andrés; Mulett-Vásquez, Jackeline (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: the aim of this study was to evaluate the sagittal inclination of implants with respect to the occlusal plane of mandibular overdentures and their effect on the prosthetic behavior of the overdentures. Methods: 52 implants were evaluated in 26 fully mandible edentulous adults (two interforaminal implants per patient), rehabilitated with ball attachments and overdenture. Cephalometric tracing was conducted, evaluating the sagittal inclination of the implant to mandibular plane (MI), occlusal plane (OI), compensation angle (CA), and anterior facial height. The following clinical variables of prosthetic behavior were assessed: the need for prosthesis rebasing, changes in prosthetic accessories, and loosening of the prosthetic attachment. The variables were described with measurements of central tendency and dispersion. Intragroup comparisons were made with the Student’s t test (p < 0.05) and correlations with the Pearson coefficient. Results: 26 patients were evaluated: 70.4% females and 29.6% males. The average age was 67.93 ± 8.6 years. The follow-up period ranged from 24 to 30 months. The average MI was 78.89 ± 10.9 degrees. There was a statistically significant correlation (r = 0.6) between MI and OI in patients who underwent a change in accessories and between MI and bone loss (r = 0.557) (p = 0.007). The average MI was higher in patients subjected to rebasing (89.70 ± 11.7 degrees), compared with those who were not subjected to rebasing (76.91 ± 9.8 degrees). A relationship with prosthetic pillar loosening could not be determined. Conclusions: the sagittal inclination of implants with respect to the occlusal plane in overdentures affects bone loss, leading to a change of accessories as well as prosthesis rebasing after two years of service